2017
DOI: 10.1017/psrm.2017.14
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Prosocial Behavior: A Multilevel Meta-Analysis

Abstract: We investigate the effect of personality on prosocial behavior in a Bayesian multilevel meta-analysis (MLMA) of 15 published, interdisciplinary experimental studies. With data from the 15 studies constituting nearly 2500 individual observations, we find that the Big Five traits of Agreeableness and Openness are significantly and positively associated with prosocial behavior, while none of the other three traits are. These results are robust to a number of different model specifications and operationalizations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 52 publications
4
41
0
3
Order By: Relevance
“…Personality Studies confirm the thesis concerning the central role of agreeableness among the personality traits triggering prosocial behaviours (here, in the form of the decision to register as a PBMD), identified as a predictor of prosocial behaviours by the researchers (Graziano and Eisenberg 1997;Bekkers 2006;Habashi et al 2016;Hill 2016;Zhao et al 2016;Kline et al 2017). Nevertheless, in the examined group, conscientiousness also occurred to be the predictor of primary importance for making the decision to register as a PBMD, the role of which so far in moderation of prosocial behaviours, including decisions to donate has been equivocal.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Personality Studies confirm the thesis concerning the central role of agreeableness among the personality traits triggering prosocial behaviours (here, in the form of the decision to register as a PBMD), identified as a predictor of prosocial behaviours by the researchers (Graziano and Eisenberg 1997;Bekkers 2006;Habashi et al 2016;Hill 2016;Zhao et al 2016;Kline et al 2017). Nevertheless, in the examined group, conscientiousness also occurred to be the predictor of primary importance for making the decision to register as a PBMD, the role of which so far in moderation of prosocial behaviours, including decisions to donate has been equivocal.…”
Section: Discussionsupporting
confidence: 67%
“…3 Algorithm of construction of decision tree CART concerning registration as PBMDvariables ordered according to their normalized importance score for tree Demir and Kumkale (2013). This is in contrast with the results obtained by Kline et al (2017), where conscientiousness was not related with prosocial behaviours, and Brown and Taylor (2015), who defined the traits of conscientiousness and neuroticim as even inversely correlated with behaviours of charity and philantrophic type (e.g., donating money and decisions to provide assistance). Nevertheless, Hill (2016), while indicating the lack of a relationship between conscientiousness and attitudes towards post-mortem organ donation and intentions to donate, suggests that this variable requires further studies (especially in the group of the young, the most desired donors), which is performed in the presented study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, openness to experience together with agreeableness are considered conceptually and empirically associated with prosocial behavior. 95 The existing literature 96 , 97 suggests that open and agreeable people are interpersonally trusting and susceptible to a view of positive outcomes in life. Since gratitude is a prosocial trait itself 98 which is felt in the context of receiving good things, it is therefore reasonable that it correlates with other prosocial traits.…”
Section: Discussionmentioning
confidence: 99%
“…It has been seen that mostly lower-class individuals are found to be more prosocial than the upper class because of their greater commitment to equalitarian views and feelings of compassion (Piff et al, 2010). However, acting prosocially, the role of personality has a strong impact on individuals' life (Kline et al, 2017) investigate the impact of personality on prosocial behavior by multi-level meta-analysis (MLMA) method and found that agreeableness and openness of big five traits have a significant impact. The main thing that motivates prosocial behavior is the fundamental personal need of living a meaningful life, therefore (Klein, N., 2017).…”
Section: Literature Reviewmentioning
confidence: 99%